1997
DOI: 10.1080/10556799708208134
|View full text |Cite
|
Sign up to set email alerts
|

Post-Perijove splitting and Lithium overabundance in Shoemaker-Levy 9 favor its planetary origin

Abstract: The SL9 nucleus splitting into 20+ fragments well after the perijove, and continuing during several months, cannot be explained by stretches due to a tidal process. Here one can track an analogy with the standard behavior of short-period comets usually developing their maximum activity after the perihelion and experiencing outbursts correlated with the solar activity. The outbursts cam also be followed by the nucleus break-up and take place at distances where water practically does not sublimate.The lithium em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The detection of spectral evidence of the presence of carbonaceous materials (carbonates and hydrogenated aromatic hydrocarbons) in the dust (Lisse et al 2005), as well as the heterogeneous and layered structure of the nucleus itself, also evidence in favour of geological evolution of the nucleus matter in the ice (water) mantle of the parental planet body (Secs. 2 & 5;Drobyshevski 1997a).…”
Section: Comparison Of DI Experiments With Conclusion Of the Old Para...mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of spectral evidence of the presence of carbonaceous materials (carbonates and hydrogenated aromatic hydrocarbons) in the dust (Lisse et al 2005), as well as the heterogeneous and layered structure of the nucleus itself, also evidence in favour of geological evolution of the nucleus matter in the ice (water) mantle of the parental planet body (Secs. 2 & 5;Drobyshevski 1997a).…”
Section: Comparison Of DI Experiments With Conclusion Of the Old Para...mentioning
confidence: 99%
“…Consider here only a few, most obvious of them (Drobyshevski 1988b(Drobyshevski , 1997a(Drobyshevski , 2000: (i) each comet has its own specific signature distinguishing it from others (A' Hearn et al 2005b); (ii) ions and radicals were observed in the coma, in the immediate vicinity of the nucleus, much closer, in fact, than it would follow from the assumption of their photolytic formation from some hypothetical "parent" molecules (particularly remarkable in this respect is the detection of atomic and ionic carbon, C and C + ); (iii) the origin of CHON dust is unclear; (iv) the laws of conservation appear to be violated; indeed, an extremely small fraction of the surface area of the nucleus (≤5-10%) receiving an as small a part of incident solar energy releases large amounts of gases and dust in the form of jets, some of the jets being active on the night side of the nucleus as well; (v) origin of the comet outbursts is unclear; moreover, in about 5% of cometary apparitions their nucleus splits into fragments flying away with velocities of up to 1-10 m/s (Sekanina 1982), and so on. This list could be continued further; suffice it to recall the anomalous long-lasting (for weeks!)…”
Section: On the Origin Of Cometsmentioning
confidence: 99%
“…It has suddenly turned out (e.g. Weaver, 2004) that a cometary nucleus is not a friable lump of snow or loose rubble pile of ~100-200 m size dirty ice 'grains', which are ready to break up under the tidal action of the Jupiter into thousands re-assembling pieces as it was assumed by Asphaug and Benz (1994) in their frequently referred paper (non-tidal scenario of the SL-9 post-perijove splitting is given by Drobyshevski, 1997). The nucleus surfaces demonstrate regions of different morphology and geological processing, layering, numerous large-scale structures, including ones resembling impact craters, etc.…”
Section: Introductionmentioning
confidence: 99%